Closed-loop geometric multi-scale heart-coronary artery model for the numerical calculation of fractional flow reserve. (September 2021) - Liu, Jincheng; Mao, Boyan; Feng, Yue; Li, Bao; Liu, Jian; Liu, Youjun
Highlights: In this study, based on the open-loop geometric FFR multi-scale simulating model, we proposed a closed-loop geometric multi-scale calculation model to simulate FFR based on the real physiological structure of the human heart. The model combines the heart module, the systemic circulation module and the coronary artery model in a complete physiological structure that can reflect the regulatory role between the heart and the coronary arteries and achieve an improved adaptability. The proposed closed-loop geometric multi-scale model is used to simulate FFR, so that the zero-dimensional lumped parameter model and the three-dimensional coronary model can be simultaneously calculated. The coordination between the two models can result in reaching a state of computational convergence during data transmission, which is consistent with the real physiological state between the human heart and coronary arteries. Between 2017 and 2020, we cooperated with Peking University People's Hospital and the Second Affiliated Hospital of Zhejiang University to perform 100 double-blind experiments of FFR to guide the PCI surgery and achieved good experimental progress. Taking the clinically measured FFR as the standard, the FFRCCT achieves an accuracy of 86% in diagnosing myocardial ischemia, a sensitivity of 62%, a specificity of 95%, a positive predictive value of 86% and a negative predictive value of 83%. Abstract: Background and objectives: Fractional flow reserve (FFR) is considered to be the "gold standard" for the clinical diagnosis of functional myocardial ischemia. With the development of medical imaging and computational fluid dynamics (CFD), noninvasive computation of FFR has been developed. The most representative calculation method is the noninvasive FFR derived from coronary CT angiography (FFRCT ), but it cannot thoroughly simulate the real physiological structure of the cardiovascular system. In this study, we propose a noninvasive closed-loop FFR derived from coronary CT angiography (FFRCCT ). Methods: The closed-loop multi-scale model includes three parts: the heart module, the coronary artery module with microcirculation structure and the systemic circulation module. The proposed structure was formed by coupling a lumped parameter model (0D) with a 3D model, such that the 0D model provides the boundary conditions for the 3D model. We enrolled 100 patients through a prospective multi-center clinical trial and calculated their FFRCCT . Then, we extracted the pressure and flow waveforms of the coronary stenosis vessels through closed-loop geometric multi-scale CFD calculations. We evaluated the accuracy of FFRCCT in diagnosing myocardial ischemia using the clinical measurement of FFR as the standard. Results: The results of FFRCCT calculation in all patients showed a good correlation between FFRCCT and FFR (r = 0.64, p < 0.05). The AUC (95% CI) of FFRCCT was 0.819 [0.72, 0.91]. The accuracy, specificity, sensitivity, positive predictive value and negative predictive value of FFRCCT were 86%, 95%, 62%, 86% and 83%, respectively. Conclusions: The closed-loop multi-scale model proposed in this study can simulate the physiological cycle in a more realistic way. FFRCCT is a reliable diagnostic index for myocardial ischemia.